Flow of a second grade fluid over a sheet stretching with arbitrary velocities subject to a transverse magnetic field - Ahmad, A.; Asghar, S. (Applied mathematics letters, 2011)
The boundary layer flow of a second grade fluid over a permeable stretching surface with arbitrary velocity and appropriate wall transpiration is investigated. The fluid is electrically conducting in the presence of a constant applied magnetic field. An exact solution to the nonlinear flow problem is presented.